A stochastic study for a generalized logistic model - Luís, Rafael (2021)
In this paper some properties of a generalized logistic discrete model are studied. Both autonomous and non-autonomous models are addressed, as well as the stochastic model, by varying the sequence of parameters that determine the sequence of mappings of the process. Some results on stability are established and the long-term behaviour of the orbits is studied.